Modified ternary positive electrode material as well as preparation method and application thereof

The double-layer clad structure of boric acid is coated by spray drying and forming a Li3BO3 and LiF, which solves the problem of unstable structure and low cycle life of the ternary positive electrode material under high voltage, and achieves higher cycle stability and battery performance.

CN119637954APending Publication Date: 2025-03-18WANXIANG 123 CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510001656.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ternary positive electrode materials have problems such as structural instability, poor thermal stability, and low cycle life at high voltages, and the coating method is low and the coating particles are prone to fall off.

Method used

Boric acid is uniformly coated on the surface of the ternary positive electrode material by spray drying, and a double-layer clad structure of Li3BO3 and LiF is formed through two heat treatments to enhance the structural stability and cyclic performance of the material.

Benefits of technology

It improves the cycling stability and thermal stability of the ternary positive electrode material at high voltages, extends the cycle life of the battery, and improves the Coulomb efficiency and capacity retention rate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a modified ternary positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The preparation method of the modified ternary positive electrode material comprises the following steps: preparing a ternary positive electrode material C through a one-step precipitation method; dispersing boric acid in a solvent to form a solution, uniformly coating the boric acid on the surface of the ternary positive electrode material C through a spray drying method, and performing heat treatment to obtain a Li3BO3-coated ternary positive electrode material D; and uniformly mixing the ternary positive electrode material D with ammonium fluoride, and carrying out heat treatment to obtain the LiF and Li3BO3 coated modified ternary positive electrode material. The invention provides a preparation method of a modified ternary positive electrode material. According to the preparation method, boric acid, ammonium fluoride and residual lithium salt on the surface of the ternary positive electrode material form Li3BO3 and LiF coating. Double coating of Li3BO3 and LiF has the effect of synergistically reducing residual alkali and interface chemical stability on the ternary positive electrode material, and the cycling stability of the ternary positive electrode material under high voltage is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a modified ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in electric vehicles, hybrid vehicles and large energy storage systems due to their high density, relatively low cost and environmental protection. However, with the rapid development of economy and technology, the energy and functional density of lithium-ion batteries are far lower than market expectations, and the performance of lithium-ion batteries depends largely on the performance of cathode materials. Ternary cathode materials have many advantages such as high energy density, good cycle stability, cost-effectiveness, safety, processing performance and environmental friendliness by rationally matching the three elements of Ni, Mn and Co. These characteristics make it one of the most commonly used cathode materials in the current lithium battery industry.

[0003] At present, ternary positive electrode materials show three major development trends: single crystal, high voltage and high nickel. The development of positive electrode materials from polycrystalline to single crystal can improve their compaction density, cycle life, etc. However, single crystal has higher requirements for sintering process, and the high temperature sintering required for single crystal is easy to aggravate the mixing of lithium and nickel, and single crystal is also easy to cause the rate performance to decrease; high voltage, that is, increasing the cut-off voltage of charging, can increase the gram capacity of positive electrode materials, thereby increasing the energy density of lithium batteries. However, increasing the charging voltage is likely to cause surface structure reconstruction of positive electrode materials, dissolution of transition metals, oxidation of electrolytes, etc.; high nickel, ternary positive electrode materials develop from medium and low nickel to high nickel and ultra-high nickel. The main purpose of high nickel is to increase the gram capacity, but divalent nickel is difficult to oxidize in the air, which puts higher requirements on lithium source, sintering atmosphere, production equipment, etc. In addition, high nickel materials are more active, easy to react with water and oxygen in the air, poor thermal stability, low cycle life, etc.

[0004] Medium nickel high voltage is based on medium nickel ternary positive electrode materials. By increasing the voltage platform, the positive electrode releases more lithium ions at high voltage, thereby obtaining more discharge specific capacity. However, after increasing the voltage, the positive electrode material has prominent problems such as structural stability, thermal stability, safety, and oxidation of the electrolyte. In order to solve this problem of medium nickel high voltage, coating and doping are usually used to modify the ternary positive electrode material.

[0005] CN 115092977A discloses a method for preparing a ternary positive electrode material, which firstly mixes a ternary precursor with a lithium source, sintering and crushing once, then adds the crushed once sintered ternary material to a lithium hydroxide solution, stirs evenly, then adds boric acid, stirs, filters and dries to obtain a coated and modified ternary positive electrode material. However, removing the solvent by stirring and evaporating is inefficient and time-consuming; at the same time, the particles of the coating are relatively large and easy to fall off.

[0006] CN 113258072A discloses a method for preparing a nickel-cobalt-manganese positive electrode material, wherein a nickel-cobalt-manganese metal salt is placed in a reaction kettle, an alkali and a complexing agent are added, the pH is adjusted, and a Sn-doped slurry is added to carry out a coprecipitation reaction in stage I; then Ta slurry is added to carry out a coprecipitation reaction in stage II, and after the coprecipitation reaction is completed, a Sn- and Ta-doped precursor is obtained by filtering, washing, and drying. The precursor is then mixed with a lithium salt and B2O3 and sintered to obtain a positive electrode material with tin doped inside, tantalum and boron doped outside, and a lithium borate coating layer on the surface. However, dry coating using B2O3 directly mixed with the precursor can only achieve point coating, and the effect is not good. Summary of the invention

[0007] The object of the present invention is to provide a modified ternary positive electrode material with better coating effect; another object of the present invention is to provide a modified ternary positive electrode material with better coating effect; another object of the present invention is to provide a lithium ion battery with high first coulombic efficiency and capacity retention rate after 100 cycles.

[0008] The present invention discloses a method for preparing a modified ternary positive electrode material, comprising the following steps:

[0009] S1: adding a nickel source, a cobalt source and a manganese source into a solvent and dissolving them to form a mixed metal salt solution A;

[0010] S2: Under a protective gas atmosphere, a precipitant is added to the mixed metal salt solution A, and the pH of the reaction solution is adjusted to 10-12 with a pH adjuster; the precipitate precipitated by the reaction is separated, washed, and dried to obtain a precursor B;

[0011] S3: After mixing the precursor B with the lithium source, sintering is performed to obtain the ternary positive electrode material C with no surface modification;

[0012] S4: dispersing boric acid in a solvent to form a solution, uniformly coating the boric acid solution on the surface of the ternary cathode material C by a spray drying method, and obtaining a Li3BO3-coated ternary cathode material D after a first heat treatment;

[0013] S5: The ternary cathode material D is mixed evenly with ammonium fluoride, and subjected to a second heat treatment to obtain a modified ternary cathode material coated with LiF and Li3BO3.

[0014] The preparation method of the modified ternary positive electrode material disclosed by the invention can be mass-produced in all steps.

[0015] In step S1, the nickel source is one or more of nickel sulfate, nickel nitrate, nickel acetate, nickel chloride or their hydrates; the cobalt source is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt chloride or their hydrates; the manganese source is one or more of manganese sulfate, manganese nitrate, manganese acetate, manganese chloride or their hydrates.

[0016] The solvent is preferably water, which can be deionized water, ultrapure water, distilled water, or purified water.

[0017] Furthermore, in step S1, the molar ratio of the nickel source, the cobalt source and the manganese source is (1-xy):x:y, wherein 0.5≤(1-xy)≤0.7; 0≤x≤0.2; 0<y≤0.3.

[0018] Furthermore, in step S2, the protective gas is nitrogen, argon or a mixture of nitrogen and argon; the precipitant includes one or a combination of at least two of sodium hydroxide aqueous solution, sodium carbonate aqueous solution, sodium bicarbonate aqueous solution, potassium hydroxide aqueous solution, and ammonium bicarbonate aqueous solution; and the concentration of the precipitant is 1-5 mol / L.

[0019] In step S2, in a protective gas atmosphere, prevent Mn 2+ ,Co 2+ Oxidation to achieve co-precipitation of nickel, cobalt and manganese.

[0020] In step S2, a one-step co-precipitation method is used to obtain precursor B.

[0021] Furthermore, in step S2, the pH regulator is ammonia water; the concentration of the ammonia water is 1-4 mol / L.

[0022] Furthermore, in step S3, the lithium source includes one or a combination of at least two of lithium hydroxide, lithium carbonate, lithium sulfate, lithium oxalate, and lithium bicarbonate; and the molar ratio of lithium ions in the added lithium source to the precursor B is greater than 1 and less than 2.5.

[0023] Appropriate addition of excess lithium source is helpful to compensate for the lithium loss during the sintering process.

[0024] Furthermore, in step S3, the sintering temperature is 600-900° C., the sintering time is 15-24 hours, and the sintering atmosphere is air and / or oxygen.

[0025] Furthermore, in step S4, the mass ratio of the added boric acid to the mass of the ternary positive electrode material C is 0.5-2:100; the atmosphere of the first heat treatment is air and / or oxygen; the treatment temperature is 400-600° C.; and the treatment time is 5-8 h.

[0026] Boric acid is prepared into a solution and then coated on the surface of the ternary positive electrode material C by spray drying. The coated particles exist in the form of molecular level, the coating is more uniform and not easy to fall off.

[0027] First, the alkaline surface of the ternary cathode material easily reacts with H2O and CO2 in the air to form compounds such as LiOH and Li2CO3, resulting in large interface resistance and irreversible capacity loss. It also increases the storage and transportation costs of active materials, promotes the formation of HF and gaseous substances, and brings safety hazards to the use of lithium-ion batteries. Adding H3BO3 reacts with residual alkali compounds such as LiOH and Li2CO3 on the surface. Not only does it consume excess lithium products in situ, but it also forms lithium ion conductors Li3BO3. The formation of the coating layer Li3BO3 can not only improve the surface lithium ion mobility but also isolate the direct contact between the electrolyte and the active material, reducing the lattice oxygen precipitation of the interface side reaction.

[0028] Furthermore, in step S5, the mass ratio of the added ammonium fluoride to the mass of the ternary cathode material D is 0.05-0.5:100; the atmosphere of the second heat treatment is air and / or oxygen; the treatment temperature is 350-500° C.; and the treatment time is 3-5 h.

[0029] The added ammonium fluoride forms a LiF coating with the residual lithium salt after the second heat treatment. The additional fluorine coating (LiF) on the positive electrode modified by Li3BO3 hinders the decomposition of the salt (electrolyte) and prevents the by-products from triggering self-catalytic side reactions at the electrolyte-positive electrode interface, thereby inhibiting gas generation during the cycle. The possible reactions of the electrolyte are as follows:

[0030] LiPF6 → LiF + PF5 (1);

[0031] LiPF6 + H2O → LiF + 2HF + POF3 ↑ (2);

[0032] LiPF6 + Li2CO3 → 3LiF + CO2 ↑ +POF3 ↑ (3);

[0033] Li2CO3 + 2HF → 2LiF + H2O + CO2 ↑ (4);

[0034] LiOH + HF → LiF + H2O (5).

[0035] In the above reaction, LiF, CO2, and H2O are produced, but the additionally coated LiF can change the chemical equilibrium, inhibit the progress of these side reactions, and thus reduce the generation of gas.

[0036] The present invention also discloses a modified ternary positive electrode material, which is obtained using the preparation method described above.

[0037] The modified ternary positive electrode material has a residual LiOH content of less than 450 ppm and a residual Li2CO3 content of less than 130 ppm.

[0038] The present invention also discloses a lithium-ion battery, comprising a negative electrode plate, an electrolyte, a separator and a positive electrode plate made of the modified ternary positive electrode material as described above.

[0039] The lithium-ion battery has an initial coulombic efficiency greater than 90% and a capacity retention rate greater than 95% after 100 cycles.

[0040] The present invention provides a method for preparing a modified ternary positive electrode material. First, the coated boric acid consumes the residual lithium salt on the surface of the positive electrode material, and forms a lithium ion conductor Li3BO3 coating layer in situ, which not only promotes the charge transfer at the interface, but also blocks the direct contact between the electrolyte and the active material of the positive electrode material, thereby reducing the interface side reaction and lattice oxygen evolution. The coated LiF layer can hinder the decomposition of the electrolyte lithium salt, prevent the byproducts from triggering the self-catalytic side reaction at the electrolyte-positive electrode interface, and inhibit the gas generation during the cycle. Therefore, the double coating of Li3BO3 and LiF on the ternary positive electrode material has the effect of synergistically reducing the residual alkali and the interface chemical stability, thereby improving the cycle stability of the ternary positive electrode material under high voltage. DETAILED DESCRIPTION

[0041] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.

[0042] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased through regular channels.

[0043] Example 1

[0044] Preparation of modified ternary cathode materials:

[0045] S1: Under nitrogen atmosphere, nickel source, cobalt source and manganese source were prepared into a mixed metal salt solution A of nickel (1.2 mol / L), cobalt (0.4 mol / L) and manganese (0.4 mol / L) in a metal molar ratio of 60:20:20. The mixed metal salt solution A, 2 mol / L NaOH solution and concentrated ammonia solution were continuously pumped into a 10L reactor, and the pH value of the reaction solution was adjusted to 11.2.

[0046] S2: The reaction liquid flows continuously from the overflow port into the aging reactor, and is washed by a vacuum filter and dried in a blast drying oven to obtain a precursor B. The molecular formula of the precursor is (Ni 60 Co 20 Mn 20 )(OH)2.

[0047] S3: Accurately weigh 150.0 g of the precursor B obtained in step S2, mix the precursor B and lithium carbonate in a high-speed mixer at a molar ratio of 1:1.1 for 30 minutes, heat the mixture to 780°C at a heating rate of 5°C / min in an air atmosphere, treat for 18 hours, and sinter to obtain the ternary positive electrode material C with unmodified surface.

[0048] S4: Accurately weigh 100.0 g of the ternary positive electrode material C and 2.0 g of H3BO3 obtained in step S3, dissolve H3BO3 with deionized water, coat the surface of the weighed ternary positive electrode material C with the boric acid aqueous solution by spray drying, and obtain powder, heat treat the powder at 550°C in an air atmosphere for 6 h, cool naturally, and obtain Li3BO3-coated ternary positive electrode material D after air flow crushing.

[0049] S5: Accurately weigh the ternary positive electrode material D obtained in step S4: 100.0 g, NH4F: 0.2 g, mix the weighed ternary positive electrode material D and ammonium fluoride evenly, place it in an air atmosphere for heat treatment at 350°C for 4 hours, cool it naturally, and obtain a modified ternary positive electrode material coated with LiF and Li3BO3 after air flow crushing.

[0050] Comparative Example 1

[0051] Preparation of ternary cathode materials:

[0052] (1) Under nitrogen atmosphere, nickel source, cobalt source and manganese source were prepared into a mixed metal salt solution of nickel (1.2 mol / L), cobalt (0.4 mol / L) and manganese (0.4 mol / L) in a metal molar ratio of 60:20:20. The mixed metal salt solution, 2 mol / L NaOH solution and concentrated ammonia water were continuously pumped into a 10 L reactor, and the pH value of the reaction solution was adjusted to 11.2.

[0053] (2) The reaction liquid continuously flows into the aging reactor from the overflow port, and is washed by a vacuum filter and dried in a blast drying oven to obtain a precursor. The molecular formula of the precursor is (Ni 60 Co 20 Mn 20 )(OH)2.

[0054] (3) Accurately weigh 150.0 g of the precursor obtained in step (2), and mix the precursor B and lithium carbonate in a high-speed mixer at a molar ratio of 1:1.1 for 30 min. Place the mixture in an air atmosphere, heat it to 780°C at a rate of 5°C / min, and heat treat it for 18 h to obtain a primary sintered product.

[0055] (4) Accurately weigh 100 g of the primary sintering product obtained in step (3), heat treat it at 550° C. for 6 h in an air atmosphere, cool it naturally, and then air flow pulverize it to obtain an uncoated modified ternary positive electrode material.

[0056] Comparative Example 2

[0057] Preparation of Li3BO3-coated ternary cathode materials:

[0058] (1) Under nitrogen atmosphere, nickel source, cobalt source and manganese source were prepared into a mixed metal salt solution of nickel (1.2 mol / L), cobalt (0.4 mol / L) and manganese (0.4 mol / L) in a metal molar ratio of 60:20:20. The mixed metal salt solution, 2 mol / L NaOH solution and concentrated ammonia water were continuously pumped into a 10 L reactor, and the pH value of the reaction solution was adjusted to 11.2.

[0059] (2) The reaction liquid continuously flows into the aging reactor from the overflow port, and is washed by a vacuum filter and dried in a blast drying oven to obtain a precursor. The molecular formula of the precursor is (Ni 60 Co 20 Mn 20 )(OH)2.

[0060] (3) Accurately weigh 150.0 g of the precursor obtained in step (2), mix the precursor and lithium carbonate in a high-speed mixer at a molar ratio of 1:1.1 for 30 min, heat the mixture to 780° C. at a heating rate of 5° C. / min in an air atmosphere, treat for 18 h, and sinter to obtain a ternary positive electrode material with an unmodified surface.

[0061] (4) Accurately weigh 100 g of the ternary positive electrode material C and 2.0 g of H3BO3 obtained in step S3, dissolve H3BO3 in deionized water, coat the weighed surface of the ternary positive electrode material C with the boric acid aqueous solution by spray drying, and obtain powder. Heat treat the powder at 550°C for 6 h in an air atmosphere, cool naturally, and obtain the Li3BO3-coated ternary positive electrode material after air flow pulverization.

[0062] Comparative Example 3

[0063] Preparation of ternary cathode materials:

[0064] (1) Under nitrogen atmosphere, nickel source, cobalt source and manganese source were prepared into a mixed metal salt solution of nickel (1.2 mol / L), cobalt (0.4 mol / L) and manganese (0.4 mol / L) in a metal molar ratio of 60:20:20. The mixed metal salt solution, 2 mol / L NaOH solution and concentrated ammonia water were continuously pumped into a 10 L reactor, and the pH value of the reaction solution was adjusted to 11.2.

[0065] (2) The reaction liquid continuously flows into the aging reactor from the overflow port, and is washed by a vacuum filter and dried in a blast drying oven to obtain a precursor. The molecular formula of the precursor is (Ni 60 Co 20 Mn 20 )(OH)2.

[0066] (3) Accurately weigh 150.0 g of the precursor obtained in step (2), and mix the precursor B and lithium carbonate in a high-speed mixer at a molar ratio of 1:1.1 for 30 min. Place the mixture in an air atmosphere, heat it to 780°C at a rate of 5°C / min, and heat treat it for 18 h to obtain a primary sintered product.

[0067] (4) Accurately weigh 100.0 g of the primary sintering product obtained in step (3), heat treat it at 550° C. for 6 h in an air atmosphere, cool it naturally, and then air flow pulverize it to obtain an uncoated modified ternary positive electrode material.

[0068] (5) Accurately weigh 100.0 g of the ternary positive electrode material obtained in step (4) and 0.2 g of NH4F. Mix the weighed ternary positive electrode material D and ammonium fluoride evenly, heat treat at 350°C for 4 h in an air atmosphere, cool naturally, and obtain a LiF-coated ternary positive electrode material after air flow pulverization.

[0069] Performance Test:

[0070] 1. The positive electrode materials obtained in Example 1 and Comparative Examples 1-3 were used as working electrodes, and the residual alkali content of the positive electrode materials was tested by potentiometric titration. The results are shown in Table 1.

[0071] Table 1 Test results of residual alkali content of Example 1 and Comparative Examples 1-3

[0072] Comparative Example 1 (unmodified) <![CDATA[Comparative Example 2 (Li3BO3 coating)]]> Comparative Example 3 (LiF coating) <![CDATA[Example 1 (Coated with LiF and Li3BO3)]]> LiOH (ppm) 651 642 598 429 <![CDATA[Li2CO3(ppm)]]> 1603 1490 1569 1235

[0073] As shown in Table 1, compared with Comparative Examples 1-3, the positive electrode material obtained in Example 1 has the least residual LiOH and Li2CO3.

[0074] 2. Evaluate the electrical properties of the ternary cathode materials obtained in Example 1 and Comparative Examples 1-3 by assembling button batteries. Using NMP as the solvent, slurry dispersion, coating and baking were performed according to the mass formula of ternary cathode material: conductive agent: PVDF = 94:3:3. Using lithium sheets as negative electrodes and conventional electrolytes, CR2025 type button batteries were assembled to evaluate their electrical properties. The discharge capacity and cycle performance in the voltage range of 2.5-4.3V were tested at room temperature of 25°C. The test results are shown in Table 2.

[0075] Table 2 Electrochemical performance test results of Example 1 and Comparative Examples 1-3

[0076] sample First cycle reversible capacity First coulombic efficiency Capacity retention after 100 cycles Comparative Example 1 160.1mAh / g 87.0% 92.2% Comparative Example 2 164.2mAh / g 87.3% 92.6% Comparative Example 3 163.8mAh / g 88.9% 93.7% Example 1 168.7mAh / g 90.5% 95.4%

[0077] As shown in Table 2, the electrochemical performance of the uncoated ternary cathode material of Comparative Example 1 is the worst among all cathode materials. Compared with Comparative Examples 2-3, the electrochemical performance of the modified ternary cathode material coated with LiF and Li3BO3 is the best.

[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a modified ternary positive electrode material, characterized in that: The following steps are involved: S1: adding a nickel source, a cobalt source and a manganese source into a solvent and dissolving them to form a mixed metal salt solution A; S2: Under a protective gas atmosphere, a precipitant is added to the mixed metal salt solution A, and the pH of the reaction solution is adjusted to 10-12 with a pH adjuster; the precipitate precipitated by the reaction is separated, washed, and dried to obtain a precursor B; S3: After mixing the precursor B with the lithium source, sintering is performed to obtain the ternary positive electrode material C with no surface modification; S4: dispersing boric acid in a solvent to form a solution, uniformly coating the boric acid solution on the surface of the ternary cathode material C by a spray drying method, and obtaining a Li3BO3-coated ternary cathode material D after a first heat treatment; S5: The ternary positive electrode material D is mixed evenly with ammonium fluoride, and subjected to a second heat treatment to obtain a modified ternary positive electrode material coated with LiF and Li3BO3.

2. The method for preparing a modified ternary cathode material according to claim 1, characterized in that: In the step S1, the molar ratio of the nickel source, the cobalt source and the manganese source is 1-xy:x:y, wherein 0.5≤1-xy≤0.7; 0≤x≤0.2; 0<y≤0.

3.

3. The method for preparing a modified ternary cathode material according to claim 1, characterized in that: In step S2, the protective gas is nitrogen, argon or a mixture of nitrogen and argon; the precipitant includes one or a combination of at least two of sodium hydroxide aqueous solution, sodium carbonate aqueous solution, sodium bicarbonate aqueous solution, potassium hydroxide aqueous solution, and ammonium bicarbonate aqueous solution; the concentration of the precipitant is 1-5 mol / L.

4. The method for preparing a modified ternary cathode material according to claim 3, characterized in that: In step S2, the pH adjuster is ammonia water; the concentration of the ammonia water is 1-4 mol / L.

5. The method for preparing a modified ternary cathode material according to claim 1, characterized in that: In step S3, the lithium source includes one or a combination of at least two of lithium hydroxide, lithium carbonate, lithium sulfate, lithium oxalate, and lithium bicarbonate; the molar ratio of lithium ions in the added lithium source to the precursor B is greater than 1 and less than 2.

5.

6. The method for preparing a modified ternary cathode material according to claim 5, characterized in that: In the step S3, the sintering temperature is 600-900° C., the sintering time is 15-24 hours, and the sintering atmosphere is air and / or oxygen.

7. The method for preparing a modified ternary cathode material according to claim 1, characterized in that: In step S4, the mass ratio of the added boric acid to the mass of the ternary positive electrode material C is 0.5-2:100; the atmosphere of the first heat treatment is air and / or oxygen; the treatment temperature is 400-600° C.; and the treatment time is 5-8 hours.

8. The method for preparing a modified ternary cathode material according to claim 1, characterized in that: In the step S5, the mass ratio of the added ammonium fluoride to the mass of the ternary positive electrode material D is 0.05-0.5:100; the atmosphere of the second heat treatment is air and / or oxygen; the treatment temperature is 350-500° C.; and the treatment time is 3-5 hours.

9. A modified ternary cathode material, characterized in that: The method is obtained by using the preparation method described in any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: It comprises a negative electrode plate, an electrolyte, a separator and a positive electrode plate made of the modified ternary positive electrode material as claimed in claim 9.

Citation Information

Patent Citations

  • Nickel-cobalt-manganese positive electrode material and preparation method thereof

    CN113258072A

  • Modified high nickel ternary cathode material and preparation method and application thereof

    CN108832103A

  • Modified ternary positive electrode material as well as preparation method and application thereof

    CN115207322A

  • Double-coated modified high-nickel ternary positive electrode material and preparation method thereof

    CN118572060A